Heat stability of Bacillus cereus enzymes within spores and in extracts. - Warth, A D (1980)
Inactivation rates for nine enzymes extracted from Bacillus cereus spores were measured at several temperatures, and the temperature at which each enzyme had a half-life of 10 min (inactivation temperature) was determined. Inactivation temperatures ranged from 47 degrees C for glucose 6-phosphate dehydrogenase to 70 degrees C for leucine dehydrogenase, showing that spore enzymes were not unusually heat stable. Enzymes extracted from vegetative cells of B. cereus had heat stabilities similar to the respective enzymes from spores. When spores were heated and the enzymes were subsequently extracted and assayed, inactivation temperatures for enzymes within the spore ranged from 86 degrees C for glucose 6-phosphate dehydrogenase to 96 degrees C for aldolase. The internal environment of the spore raised the inactivation temperature of most enzymes by approximately 38 degrees C. Loss of dipicolinic acid from spores was initially slow compared with enzyme inactivation but increased rapidly with longer heating. Viability loss was faster than loss of most enzyme activities and faster than dipicolinic acid release.